Assessment of IT Risk Management at the Faculty of Industrial Engineering, Telkom University, Utilizing the COBIT 2019 Framework's APO12 Domain with LAM INFOKOM Standards Mapping - Ayu, Adinda Laras; Lubis, Muharman; Abdurrahman, Lukman; Zamzami, Ikhlas Fuad; Alqahtani, Raied Ali; Ramadhani, Rafian (Electronic Integrated Computer Algorithm Journal, 2024)
In the era of rapid technological development, Information Technology (IT) plays a critical role in the operational aspects of companies/organizations, including educational institutions like Telkom University. The proper implementation of IT can enhance system efficiency and integration within an institution. IT Governance aims to ensure that the measurement of effectiveness and efficiency within an agency aligns with its strategic goals. Telkom University, especially the Faculty of Industrial Engineering, is one of the educational institutions focusing on the development of Information Technology to ensure that the information systems and technologies used in academic activities are effective. COBIT 2019 is a framework developed by ISACA to organize and implement strategies in information management and governance with international standards. In this analysis, the focus is on the APO12 domain of COBIT 2019, which plays a role in IT risk management. The Faculty of Industrial Engineering also requires standardization with LAM-INFOKOM, an accreditation body that establishes standards for risk management in informatics and computer science. This research aims to map the standards of LAM-INFOKOM and COBIT 2019 to determine the capability level of Risk Management. Additionally, it aims to provide recommendations for potential improvements in three aspects: people, process, and technology. The expected outcome of this research is to enhance risk management at the Faculty of Industrial Engineering, Telkom University, to align with LAM-INFOKOM standards and the institution's vision and mission. The results of the IT Risk Management analysis using the COBIT 2019 framework can also serve as a structured approach for other universities in improving IT Governance.